Working with smallholder dairy producers on feeding dairy cattle in western Kenya - Mwendia, Solomon W.; Odhiambo, Ruth; Notenbaert, An Maria Omer (Bioversity International and the International Center for Tropical Agriculture, 2020)
We worked with selected dairy farmers in Western Kenya counties (Bungoma, Busia, Kakamega) on feeding lactating cattle and monitored milk output. Two feeding phases comprised, following farmer own practice on what they normally do on daily basis, and two, introduced forages not normally used in the area namely Panicum Maasai and Brachiaria Mulato II. Under either case, we observed milk production (liters). Generally, there was a mix of some animals increasing milk production and a drop in others. The animals increased milk production by up to 9.5% when the two introduced grasses were compared to farmers practice. However, Panicum Maasai has greater increase in production of up to 31% while Mulato II on its own did not register milk increase with the animals used and is worth investigating more. Use of improved forages for increased livestock productivity require concerted effort on promotion and awareness creation while ensuring availability of seeds/planting materials is adequate to reach adoption at scale.